1992
DOI: 10.1139/o92-151
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor activity during cellular aging of human diploid fibroblasts

Abstract: Human diploid fibroblasts display a limited proliferative life span in vitro, which is directly correlated to the age of the donor from which the cells were explanted. In an effort to identify molecular events that may underlie the loss of proliferative potential in aging fibroblasts, we have determined, at the protein level, the abundance of several cell-cycle-regulated proteins and the activity of the two major members of the activator protein-1 (AP-1) DNA binding complex. We find that cyclin A and p34cdc2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…DISCUSSION Previous studies have shown that the activity of the transcription factor Fos is required for the growth of fibroblast cells in culture (19,22,32,37). Senescent cells that are unable to grow in response to mitogens express much lower levels of Fos in response to serum stimulation, and Fos proteins that are expressed appear to be much more heavily phosphorylated and fail to bind DNA (34,35,46). In the present study, we show that SRF, a transcription factor that is known to be required Several lines of evidence suggest that the loss of SRE binding activity is not due to a nonspecific artifact of protein isolation from senescent cells.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…DISCUSSION Previous studies have shown that the activity of the transcription factor Fos is required for the growth of fibroblast cells in culture (19,22,32,37). Senescent cells that are unable to grow in response to mitogens express much lower levels of Fos in response to serum stimulation, and Fos proteins that are expressed appear to be much more heavily phosphorylated and fail to bind DNA (34,35,46). In the present study, we show that SRF, a transcription factor that is known to be required Several lines of evidence suggest that the loss of SRE binding activity is not due to a nonspecific artifact of protein isolation from senescent cells.…”
Section: Resultsmentioning
confidence: 91%
“…For the majority of cellular genes examined, changes in expression have been found to be minimal. For example, the expression of genes encoding actin, ornithine decarboxylase, c-Myc, pl05Rb, and Jun, among others (34,35,39,46,47,56), decreases by s50% as cells become senescent. In contrast, considerable changes in expression levels have been observed for a subset of growth-related genes such as those encoding insulin-like growth factor (IGF)-binding protein 3, cyclin D1, cdc2, cdk2, cyclin A, the A chain of platelet-derived growth factor, cyclin B, and Fos (2,10,23,31,34,38,48,(54)(55)(56).…”
mentioning
confidence: 99%
“…The primary nuclear function of C subunit is regulation of genes via phosphorylation of the nuclear (Waeber and Habener, 1991) transcription factors of the CREB/ATF family. Microinjection of purified C subunit is sufficient to stimulate phosphorylation of CREB (Meinkoth, unpublished data) and induce CREregulated gene expression (Riabowol, 1992). Diffusion of the C subunit in and out of the nucleus links the cytoplasmic and nuclear functions of cAMP via a simple and reliable, though noninstantaneous Hagiwara et al, 1993), mechanism, which must be understood before considering possible modulation of such signal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A simplistic view of the involvement of tumor suppressors such as pRb and p53 in cellular senescence would be that their overexpression or constitutive acti vation might block cell growth as cells age in culture. In the case of pRb, it has been ob served that senescent cells fail to phosphorylate, and therefore inactivate pRb as a growth inhibitor, in response to serum stimulation Gene Expression in Aging Cells [9][10][11], Similarly, the activity of p53 was ob served to increase in senescent cells in the absence of increased expression, indicating that constitutive activation of this potent tu mor suppressor may contribute significantly to blocking proliferation in senescent cells [12], This observation is particularly interest ing in light of the finding that p53 is capable of inducing the transcription of the growth inhibitors p21CiP1/Wafl/Sdil [13] and cyclin D1 [14] which are also upregulated in senescent cells [15][16][17][18].…”
Section: Senescence As a Mechanism Of Tumor Suppressionmentioning
confidence: 99%